Al-Fihris Catalogue de Manuscrits Arabes - Sbath, Paul (Gorgias Press, 2012)
These three volumes describe over 3,000 Arabic works from more than 1,000 authors, including several hundred anonymous works
Description based on online resource; title from PDF title page (publisher's Web site, viewed 10. Jan 2022)
Keywords: REFERENCE / Catalogs